PERUMUSAN STRATEGY GREEN PRODUCT GUNA MENINGKATKAN PERKEMBANGAN UMKM BERBASIS RAMAH LINGKUNGAN (Studi Pada Dinas Perindustrian dan Perdagangan UMKM Kota Magelang) - Indah Lusiana; Dian Marlina Verawati; Ivo Novitaningtyas (Universitas Mercu Buana Yogyakarta, 2021)
This study aims to formulate a green product strategy to increase the development of environmentally friendly UMKM in Magelang City. This type of research uses a qualitative approach by using primary data sources and secondary data obtained by using the methods of observation, interviews, questionnaires, and documentation. The population in this study is the Department of Industry and Trade of Magelang City using the purposive sampling technique. After the data is collected, then the data is analyzed using the IFAS and EFAS matrix SWOT analysis. The results of the analysis show that the position of the Magelang City Industry and Trade Office is in Quadrant I, so the strategy used is a strategy to support aggressive growth policies. One of them is by using the SO strategy, namely UMKM are able to maintain quality raw materials in production, UMKM can maintain product quality, monitor production operational standards, conduct guidance, and control production waste, UMKM actors start using environmentally friendly packaging or green products and increase public awareness relations to establish good relationships with consumers and partners.